Socialization of the Use of Social Media Properly and Correctly Without Violating the ITE Law for Malang City Residents - Ali, Moh.; Priyanti, Novie Ary; Habiburrahman , Novan; Puspaningsih, Eunike Sri; Lestari, Juniarti Wulan; Hariadi , Agung; Ferdinant Pakage (Universitas Kristen Cipta Wacana, 2024)
Constitution number 19 of 2016 concerning Information and Electronic Transactions (hereinafter abbreviated as